Aerial release of acarine biological control agents on carrier materials - Drukker, B.; Yaninek, John S.; Coles, R.N.; Herren, H.R. (1991)
Laboratory and field experiments were performed to test several materials on their suitability as carrier for the aerial release of phyroseiid mites. Relatively few mites adhered to the materials. Nevertheless, mites were rettieved in cassava fields after a mass release, using oat flakes as carrier material. This method can be suitable when large areas are to be supplied with low mite densities.